Effect of Cooling Rate on the Microstructure and Mechanical Properties of Low Carbon Steel - Saklakoğlu, Nurşen; Ünalp, Firat; Demir, Mehmet Cem; Hocalar, Çağlar; Demirok, Selçuk (Bánki Közlemények, 2019)
This paper reports the effect of cooling rate on the microstructure and mechanical -properties of a kind of low carbon steel microalloyed with V and Nb content (0,01%and0,0164%) after hot deformation by using real forging experiments. The results show that cooling rate has a significant effect on the microstructure, yield strength, tensile strength and impact energy of the P285NH steel. The accelareted air cooling with 1,48 oC/s cooling rate yielded to the formation of mixed structure with acicular ferrite and bainitic ferrite which resulted higher tensile strength and lower toughness. In this case, the normalization step was needed to obtain higher toughness which customer’s demand.